Swear Words in Nicki Minaj Song Lyrics - Rani Handayani Handayani (ELITE: Journal of English Language and Literature, 2016)
This thesis discussed swear words in Nicky Minaj’s song lyrics. The objectives of this research are to find out the types of swear words and the function of swear words in Nicki Minaj .'s song lyrics. The researcher used Steven Pinker’s theory (2007) to analyze the types of swear words and used Swan's theory (1995) to analyze the function of swear words. In analyzing this research, the researcher used the qualitative method to examine swear words in Nicki Minaj's song lyrics. The source of the data was collected from Nicki Minaj’s song lyric entitled Barbie dreams and Anaconda. Technique of data analyzed by presenting the data, describing the data, interpreting the data, and displaying the data. The results show that there are five types of swear words used in Nicky Minaj’s song lyrics Emphatically (2) data, Dysphemism (5) data, Idiomatically (12) data, Abusively (14) data, and Cathartically (4) data. Also, there are eight of ten functions swear words found such as Exclamation of Annoyance (7) data, Exclamation of Surprise (1) data, Insult (noun) (11) data, Insulting Request to Go Away (1) data, Expression of Unconcern (1) data, Violent Refusal (1) data, Intensifying Adjective (4) data, Miscellaneous (8) data. Two functions of swear words that were not found were the function of the swear word surprise question and the function of insult (imperative verb + object).